The gut microbiome regulates astrocyte reaction to Aβ amyloidosis through microglial dependent and independent mechanisms - Chandra, Sidhanth; Di Meco, Antonio; Dodiya, Hemraj B.; Popovic, Jelena; Cuddy, Leah K.; Weigle, Ian Q.; Zhang, Xiaoqiong; Sadleir, Katherine; Sisodia, Sangram S.; Vassar, Robert (Molecular neurodegeneration, 2023)
Background Previous studies show that antibiotic-mediated (abx) alteration of the gut microbiome (GMB) results in a reduction of amyloid beta (Aβ) plaques and proinflammatory microglial phenotype in male APPPS1-21 mice. However, the effect of GMB perturbation on astrocyte phenotypes and microglial-astrocyte communication in the context of amyloidosis has not been examined. Methods To study whether the GMB modulates astrocyte phenotype in the context of amyloidosis, APPPS1-21 male and female mice were treated with broad-spectrum abx leading to GMB perturbation. GFAP + astrocytes, plaque-associated astrocytes (PAA), PAA morphological parameters, and astrocyte complement component C3 levels were quantified using a combination of immunohistochemistry, immunoblotting, widefield microscopy, and confocal microscopy. Furthermore, these same astrocyte phenotypes were assessed in abx-treated APPPS1-21 male mice that received either fecal matter transplant (FMT) from untreated APPPS1-21 male donors to restore their microbiome or vehicle control. To assess complete absence of the GMB on astrocyte phenotypes, the same astrocyte phenotypes were quantified in APPPS1-21 male mice raised in germ-free (GF) or specific-pathogen free conditions (SPF). Lastly, we assessed whether microglia are necessary for abx-induced astrocyte phenotypes by depleting microglia in APPPS1-21 male mice via treatment with a colony-stimulating factor 1 receptor (CSF1R) inhibitor (PLX5622) and vehicle control or PLX5622 and abx. Results Herein, we demonstrate that postnatal treatment of male APPPS1-21 mice with broad-spectrum abx leading to GMB perturbation reduces GFAP + reactive astrocytes and PAAs, suggesting that the GMB plays a role in regulating reactive astrocyte induction and recruitment to Aβ plaques. Additionally, we show that compared to controls, PAAs in abx-treated male APPPS1-21 mice exhibit an altered morphology with increased number and length of processes and reduced astrocytic complement C3, consistent with a homeostatic phenotype. GFAP + astrocyte reduction, PAA reduction, astrocyte morphological changes, and C3 levels are restored when abx-treated mice are subject to FMT from untreated APPPS1-21 male donor mice. Next, we found that APPPS1-21 male mice raised in GF conditions have similar astrocyte phenotypes as abx-treated male APPPS1-21 male mice. Correlational analysis revealed that pathogenic bacteria depleted by abx correlate with GFAP + astrocytosis, PAAs, and astrocyte morphological changes. Finally, we determined that abx-mediated reduction in GFAP + astrocytosis, PAAs, and astrocytic C3 expression is independent of microglia. However, abx-induced astrocyte morphological alterations are dependent on the presence of microglia, suggesting that there is both microglial independent and dependent GMB control of reactive astrocyte phenotypes. Conclusions We show for the first time, in the context of amyloidosis, that the GMB plays an important role in controlling reactive astrocyte induction, morphology, and astrocyte recruitment to Aβ plaques. GMB regulation of these astrocytic phenotypes is both independent and dependent on microglia.